Prevalence of Infertility Among Patients With Isthmocele and Fertility Outcome After Isthmocele Surgical Treatment: A Retrospective Study - Calzolari, Stefano (Ochsner J, 2019)
Background: An isthmocele is a diverticulum on the anterior wall of the uterine isthmus at the site of a cesarean delivery scar. We evaluated the prevalence of infertility among patients with isthmocele, the resolution of symptoms, and infertility outcomes after hysteroscopic isthmoplasty. Methods: We conducted a retrospective study of 35 consecutive patients with symptomatic isthmocele between 2010 and 2015 at Hospital Piero Palagi in Florence, Italy. Patients with symptomatic isthmocele had postmenstrual abnormal uterine bleeding, sovrapubic pain, and infertility. Results: The study population was divided into Group A – Fertile Patients (n=19) and Group B – Infertile Patients (n=16) according to the prevalence of infertility after the diagnosis of isthmocele. Group B was subdivided into Group B1 (became pregnant, n=9) and B2 (did not become pregnant, n=7) according to infertility resolution after isthmocele treatment. We found statistically significant differences between Groups A and B regarding the number of cesarean sections (P=0.0205), the grade of isthmocele (P=0.0421), and body mass index (P=0.0001). In the subgroup analysis, we found statistically significant differences between Groups B1 and B2 for age (P=0.0151), grade of isthmocele (P=0.0361), and cervical dilatation (P=0.0293). Conclusion: We identified a subgroup of patients at higher risk of being infertile after the diagnosis of isthmocele and a subgroup of patients who could benefit the most in terms of fertility after minimally invasive hysteroscopic surgery.